A new technique to determine gamma emission probability above the neutron threshold without gamma-ray detectors - Imai Nobu; Dozono Masanori; Michimasa Shin’ichiro; Sumikama Toshiyuki; Ota Shinsuke; Hayakawa Seiya; Hwang Jongwon; Iribe Kotaro; Iwamoto Chihiro; Kawase Shoichiro; Kawata Keita; Kitamura Noritaka; et al. (EPJ Web of Conferences, 2025)
We have developed a new experimental technique to determine the gamma emission probability from unbound states populated by the (d, p) reaction at 20 MeV/nucleon under the inverse kinematics. This was achieved using the decelerating and focusing device OEDO at RIBF. Due to the inverse kinematics, the outgoing reaction residues can be identified by a magnetic spectrometer. By combining the missing spectroscopy with the identification of the residual ions, the γ emission channel was determined event-by-event as a function of the excitation energy, without detecting γ ray from the unbound states. As the first application, the method was used to study the neutron capture reaction on 79Se via the (d, p) reaction as a surrogate reaction for the neutron energies up to 5 MeV. Additionally, the technique was employed to investigate the compound reaction channel of (n, γ) cross sections on 130Sn.